Effect of cyclophosphamide on the immune responsiveness of jirds infected with Brugia pahangi. - Katz, S P (1984)
The in vitro immune responsiveness of lymphocytes from Brugia pahangi-infected jirds was examined after serial administration of cyclophosphamide (20 mg/kg). Cyclophosphamide had no effect on parasite burdens, anti-B. pahangi antibody titers, or suppressed spleen cell reactivity to B. pahangi antigens. Cyclophosphamide restored cellular responsiveness to the mitogens phytohemagglutinin, concanavalin A, and pokeweed mitogen.